Ac-EAZY! Towards GMP-Compliant Module Syntheses of 225Ac-Labeled Peptides for Clinical Application - Marc Pretze; Falk Kunkel; Roswitha Runge; Robert Freudenberg; Anja Braune; Holger Hartmann; Uwe Schwarz; Claudia Brogsitter; Jörg Kotzerke (MDPI AG, 2021)
The application of 225Ac (half-life T1/2 = 9.92 d) dramatically reduces the activity used for peptide receptor radionuclide therapy by a factor of 1000 in comparison to 90Y, 177Lu or 188Re while maintaining the therapeutic outcome. Additionally, the range of alpha particles of 225Ac and its daughter nuclides in tissue is much lower (47-85 μm for alpha energies Eα = 5.8-8.4 MeV), which results in a very precise dose deposition within the tumor. DOTA-conjugated commercially available peptides used for endoradiotherapy, which can readily be labeled with 177Lu or 90Y, can also accommodate 225Ac. The benefits are lower doses in normal tissue for the patient, dose reduction of the employees and environment and less shielding material. The low availability of 225Ac activity is preventing its application in clinical practice. Overcoming this barrier would open a broad field of 225Ac therapy. Independent which production pathway of 225Ac proves the most feasible, the use of automated synthesis and feasible and reproducible patient doses are needed. The Modular-Lab EAZY is one example of a GMP-compliant system, and the cassettes used for synthesis are small. Therefore, also the waste after the synthesis can be minimized. In this work, two different automated setups with different purification systems are presented. In its final configuration, three masterbatches were performed on the ML EAZY for DOTA-TATE and PSMA-I&T, respectively, fulfilling all quality criteria with final radiochemical yields of 80-90% for the 225Ac-labeled peptides.